Jockey Career Length and Risk Factors for Loss from Thoroughbred Race Riding - Kylie Legg (Sustainability, 2020)
Professional thoroughbred racing jockeys repeatedly work close to physiological capacity during races, whilst maintaining low body weights, on a daily basis with no off-season. The effects of this on their career length is unknown. The aim of this study was to examine the career lengths and reasons for loss from the industry of 674 jockeys and apprentices who rode over 14 racing seasons and 421,596 race day starts in New Zealand. Descriptors were compared between jockeys in short (1–2 years), middle (3–9 years) and long (>10 years) career cohorts with descriptive statistics and Kaplan–Meier survival curves. The median career length for jockeys was 2 years (IQR 1–6). Long career cohort jockeys (11%) had lower carried weights (IQR 56–57 kg, p = 0.03), 40 times the median number of rides per season (248, IQR 61–434, p < 0.001), half the rate per 1000 rides of falling (1.1, 95% CI 1.0–1.2, p = 0.009) and 1.3 times the rate of winning (100, 95% CI 99–101, p < 0.01) than jockeys in the short career cohort. Jockeys who rode over 200 races per season had careers three times longer than jockeys with fewer races per season (p < 0.001). Half of the 40% of jockeys who failed to complete their apprenticeship were lost from the industry in their first year of race riding. In conclusion, most jockeys had short careers where the workload of a jockey and their ability to obtain rides had greater impact on career longevity than their performance.